Implementation of Project-Based Learning Models in Senior High School Education: A Systematic Review - Pratama, Dhaifullah Mochtar Adi; Maksum, Muh. Nur Rochim; Istanto, Istanto (Universitas Muhammadiyah Surakarta, 2025)
The rapid development of twenty-first-century education has emphasized the need for innovative pedagogical models that foster both academic achievement and essential twenty-first-century skills, one of which is Project-Based Learning (PBL). Although PBL has been widely implemented and examined in primary and higher education contexts, studies focusing specifically on its implementation at the senior high school level remain limited and report inconsistent findings. This study aims to systematically review the existing literature on the implementation of Project-Based Learning in senior high school education, with particular attention to implementation models, impacts on students’ learning outcomes, challenges faced by teachers, strategies to address these challenges, and emerging research trends. A systematic literature review method was employed by searching articles indexed in the Scopus database using the keywords “Project-Based Learning,” “Secondary Education,” and “Educational Models.” The selected studies were screened based on predefined inclusion and exclusion criteria and analyzed using the PRISMA framework. The findings indicate that PBL in senior high schools is commonly implemented through interdisciplinary and contextual approaches and has a positive impact on students’ critical thinking, collaboration, creativity, and learning engagement, although its effects on academic achievement remain mixed. Major challenges in implementing PBL include limited teacher training, insufficient resources and infrastructure, time management constraints, and assessment complexities. Furthermore, recent research trends highlight increased integration of advanced technologies, including artificial intelligence, inter-institutional collaboration, and a growing emphasis on process-oriented assessment and the development of twenty-first-century skills. Overall, this review suggests that Project-Based Learning holds substantial potential to enhance the quality of learning in senior high school education; however, its effective implementation requires systematic planning, sustained teacher professional development, and strong institutional support.